Noninvasive prenatal diagnosis of monogenic diseases by digital size selection and relative mutation dosage on DNA in maternal plasma - Fiona M.F. Luna (2018)
Prenatal diagnosis of monogenic diseases, such as cystic fibrosis and β-thalassemia, is currently offered as part of public health programs. However, current methods based on chorionic villus sampling and amniocentesis for obtaining fetal genetic material pose a risk to the fetus. Since the discovery of cell-free fetal DNA in maternal plasma, the noninvasive prenatal assessment of paternally inherited traits or mutations has been achieved. Due to the presence of background maternal DNA, which interferes with the analysis of fetal DNA in maternal plasma, noninvasive prenatal diagnosis of maternally inherited mutations has not been possible. Here we describe a digital relative mutation dosage (RMD) approach that determines if the dosages of the mutant and wild-type alleles of a disease-causing gene are balanced or unbalanced in maternal plasma. When applied to the testing of women heterozygous for the CD41/42 (-CTTT) and hemoglobin E mutations on HBB, digital RMD allows the fetal genotype to be deduced. The diagnostic performance of digital RMD is dependent on interplay between the fractional fetal DNA concentration and number of DNA molecules in maternal plasma. To achieve fetal genotype diagnosis at lower volumes of maternal plasma, fetal DNA enrichment is desired. We thus developed a digital nucleic acid size selection (NASS) strategy that effectively enriches the fetal DNA without additional plasma sampling or experimental time. We show that digital NASS can work in concert with digital RMD to increase the proportion of cases with classifiable fetal genotypes and to bring noninvasive prenatal diagnosis of monogenic diseases closer to reality. © 2008 by The National Academy of Sciences of the USA.